Pengaruh Kepemimpinan Transformasional, Komunitas Belajar Dan Budaya Sekolah Terhadap Kualitas Pembelajaran di SMP Negeri Sewilayah Sukorejo Kabupaten Kendal - Warsiyatun Warsiyatun; Ngasbun Egar; Aryo Andri (Cetta: Jurnal Ilmu Pendidikan, 2026)
Learning quality is a measure of the effectiveness of the learning process in achieving predetermined goals. The objectives of this study are to analyze the collective influence of transformational leadership, learning communities, and school culture on learning quality. The research approach used a quantitative survey method. The research type was correlational. The study population was 238 teachers, and the sample size was 149 teachers. Data collection was conducted using a questionnaire. Data analysis techniques included descriptive data analysis, swimmer's tests, including normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests, and hypothesis testing, including simple and multiple linear regression. The results of the study show that: 1) Transformational leadership has a strong and significant influence on the quality of learning by 76.4%. 2) Learning community has a strong and significant influence on the quality of learning by 74.3%. 3) School culture has a strong and significant influence on the quality of learning by 75.3%. 4) Transformational leadership, learning community and school culture have a strong and significant influence on the quality of learning by 75.6%. Then the correlation coefficient value r is 0.746.